Impact of Management Control Systems on Managerial Job Satisfaction and Stress in Local Government: The Mediating Role of Organizational Commitment - Silaban, Adanan; Siagian, Nalom; Sitorus, Sunday Ade; Medrofa, Daud (International Journal of Economics Development Research (IJEDR), 2024)
Management Control Systems (MCS) are an important part of the operations of public sector organizations. However, the implementation of MSS can have consequences on the well-being of public managers such as job satisfaction and stress. One important dimension of MSS is the clarity of the public manager's role. The role of public managers is a very important part of the organization, because public managers have the task of planning, organizing, directing and controlling organizational activities. These tasks require role clarity, where public managers must provide accurate, complete, clear and relevant information to their users. Therefore, the clarity of the role of public managers is thought to have an effect on the job satisfaction and stress of public managers. This research is important to do considering that SPM is a tool used in achieving organizational goals, and therefore it is also necessary to gain knowledge of its consequences on the welfare of public managers. Empirical evidence on this subject is still very limited, especially in public sector organizations in Indonesia. This study aims to empirically examine the effect of role clarity on job satisfaction and stress of public managers and the mediation of organizational commitment in public sector organizations. The results of this study are useful theoretically and practically. Theoretically, it enriches the SPM literature on the effect of management control in the form of the impact of role clarity on job satisfaction and stress levels of public public managers. Practically, the results of this study can be used as guidelines in the design of SPM that can increase public managers' job satisfaction and stress and organizational commitment.  The research was conducted using a survey method to public managers at the Regional Apparatus Organization (ODP) of Medan City Government.